AN OVERVIEW OF USING PRAGMATIC STUDY AMONG EFL/ESL UNIVERSITY LEARNERS - Younis Salih Fatah, Noor Mala BT Ibrahim, Tina Binti Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Speech acts and pragmatics have a crucial role in analyzing texts, speeches, and utterances in both written and spoken discourse. Currently, pragmatics has a significant role in the written text. Since there are some issues and difficulties face by university TEFL, EFL/ESL students, and learners in analyzing texts and speeches, the issues might be due to not understanding the texts real meaning. These problems and issues need to be treated and encouraged to focus on the structure and inside the meaning of texts while analyzing and searching for texts real purpose rather than the other literal and surface sense. This is better to understand the notion of texts, speeches, and utterances. Hence, the study shows and explains the importance of pragmatics and the theories investigated by previous researchers and scholars. The paper also offers some present studies on the effect of pragmatic use in class and the importance of using pragmatics in literary texts that benefit for TEFL students in analyzing texts and utterances. The purpose of this paper is to provide and explain a brief overview of the theory of language use, the concepts of pragmatics, and pragmatics application of text and literature to give familiarity to the students with text analysis and understanding. From this perspective, the methodological and framework used in the present study is Austin's language theory by following a pragmatic analytical by applying pragmatic aspects, including Speech act theory implicature, and conversational analysis. This would be supported by several and different studies that have been analyzing texts of the target language. Another important aim of this paper is to show the effect of teaching/ learning pragmatics on TEFL, EFL/ESL learners' questions of the target language to analyze and interpret texts.